The association between geographical factors and dental caries in a rural area in Mexico - Gerardo Maupome; E. Angeles Martínez-Mier; Alanna Holt; Carlo Eduardo Medina-Solís; Andrés Mantilla-Rodríguez; Brittany Carlton (Cadernos de Saúde Pública, 2013)
The aim of this study was to investigate the association between markers of oral disease and geographical factors influencing access to dental care (DMFT score) among school children in Central Mexico. Retrospective data were collected during an international service-learning program between 2002 and 2009. A sample of 1,143 children (55% females; mean age 12.7±13.1years) was analyzed. The mean DMFT score, represented largely by untreated tooth decay, was 4.02 (4.76). The variables that had the most significant effect on the DMFT score were proportion of paved roads between the community and dental services, and the availability of piped potable water. The DMFT score increased in proportion to the percentage of paved roads. In contrast, the DMFT score decreased with the availability of piped potable water. Similar results were found for untreated tooth decay. The main variable associated with a significant increase in dental fillings was proportion of paved roads. Together with Brazilian reports, this is one of the first investigations of the association between geographical factors and oral health in an underdeveloped setting.